2021
DOI: 10.1093/humrep/deaa304
|View full text |Cite
|
Sign up to set email alerts
|

High birth weight and large-for-gestational-age in singletons born after frozen compared to fresh embryo transfer, by gestational week: a Nordic register study from the CoNARTaS group

Abstract: STUDY QUESTION When do the differences in birth weights become apparent between singletons born after frozen embryo transfer (FET) and fresh embryo transfer (fresh ET)? SUMMARY ANSWER Mean birth weights after FET become significantly higher starting from gestational week (GW) 33 among boys and from GW 34 among girls. WHAT IS KNOWN ALREADY In recent years, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Our results for fresh ET and FET are consistent with previous studies showing smaller birth weight in offspring conceived via fresh ET compared with those who were NC, and higher birth weight and large-for-gestational-age in offspring conceived via FET compared with those conceived via fresh ET. 12,13 Our study also agrees with results from a UK record linkage study that assessed birth size and body size at ages 6 to 8 weeks and 5 years in offspring born between 1997 and 2009, Parents were classified as fertile if time to pregnancy within 12 months from when they began trying; parents were classified as subfertile if time to pregnancy was greater than 12 months. Cohort-specific results were adjusted for maternal age, parity, body mass index (BMI), smoking, education, ethnicity or country of birth, plus offspring sex and age.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results for fresh ET and FET are consistent with previous studies showing smaller birth weight in offspring conceived via fresh ET compared with those who were NC, and higher birth weight and large-for-gestational-age in offspring conceived via FET compared with those conceived via fresh ET. 12,13 Our study also agrees with results from a UK record linkage study that assessed birth size and body size at ages 6 to 8 weeks and 5 years in offspring born between 1997 and 2009, Parents were classified as fertile if time to pregnancy within 12 months from when they began trying; parents were classified as subfertile if time to pregnancy was greater than 12 months. Cohort-specific results were adjusted for maternal age, parity, body mass index (BMI), smoking, education, ethnicity or country of birth, plus offspring sex and age.…”
Section: Discussionsupporting
confidence: 86%
“… 6 , 7 , 8 , 9 Furthermore, studies comparing ART procedures suggest perinatal differences between IVF and ICSI, 10 and fresh embryo transfers (ET) and frozen-thawed ET (FET). 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Our results for fresh ET and FET are consistent with previous studies showing smaller birth weight in fresh ET compared with NC, and higher birth weight and large-for-gestational-age in FET compared with fresh ET (12, 13). Our study also agrees with results from a UK record linkage study that assessed birth size and body size at 6-8 weeks and 5 years in offspring born between 1997-2009, showing that compared with NC, offspring born by fresh embryos were lighter, and those born by FET were heavier at birth and 6-8 weeks, and that all groups had similar weight at 5 years (16).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a significantly higher risk for birth weight >4,500 g was observed by other large-scale studies with the HRT protocol than with the modified-NC regimen (183,185). A large retrospective Nordic register-based cohort study reported that, when compared with natural conceptions, the mean birth weight of FET pregnancies become significantly higher starting from gestational week 33 among boys and from gestational week 34 among girls (193).…”
Section: Maternal and Obstetric Outcomes After Different Fet Protocolsmentioning
confidence: 90%